MORPHOFUNCTIONAL FEATURES OF THE DEVELOPMENT OF VARIOUS TYPES OF MARTIAL ARTS IN ATHLETES - Taghizoda Sagdiana Mahir kizi; Tulyaganova F.M; Taraleva T.A; Zamaliddinova R.S (Proximus Journal Publishing, 2024)
Mixed martial arts (SBI) is a mixture of various martial arts, which includes 2 subtypes: percussion, which include boxing, kickboxing, muay, etc., and grappling: judo, Greco-Roman wrestling, freestyle wrestling, etc., which became popular in the 1990s. UBIs are physiologically challenging sports that can tax all energy health systems. Therefore, endurance strength, maximum strength, power, aerobic and anaerobic power are important to maintain performance during a match. In addition, the technical and tactical aspects of the battle are crucial. In fact, the most successful athletes combine Elite-level skills with extraordinary levels of strength and fitness. Due to the fact that mixed martial arts athletes are divided into body weight categories, weight loss is an extremely common method in athletes. Therefore, body composition control is necessary to determine the best weight category of athletes without the need for aggressive weight loss processes. In addition, higher levels of body fat negatively affect locomotion performance, technique, lower limb muscle strength, and endurance strength
Keywords: assessment; strength; endurance